Exploring The Triad: Unveiling The Relationship Between Job Characteristics, Job Satisfaction, And Employee Performance - Fika Rahmanita; Najmudin Najmudin; Sudarto Sudarto (International Journal of Economics, Business and Innovation Research, 2024)
This research was conducted to determine the relationship between job characteristics, job satisfaction and lecturer performance. This research was carried out using a research method based on a quantitative approach which was developed using the causality method and SEM-PLS as a data analysis method. The research results show that there are variables that have a strong relationship to performance, namely job characteristics and job satisfaction. The findings show that job characteristics have a strong relationship with performance and job characteristics have a strong relationship with job satisfaction.